Information Retrieval Document Classified with K-Nearest Neighbor - Alifian Sukma; Badruz Zaman; Endah Purwanti (Record and Library Journal, 2018)
Along with the rapid advancement of technology development led to the amount of information available is also increasingly abundant. The aim of this study was to determine how the implementation of information retrieval system in the classification of the journal by using the cosine similarity and K-Nearest Neighbor (KNN).